2022
DOI: 10.7554/elife.82031
|View full text |Cite
|
Sign up to set email alerts
|

T cells modulate the microglial response to brain ischemia

Abstract: Neuroinflammation after stroke is characterized by the activation of resident microglia and the invasion of circulating leukocytes into the brain. Although lymphocytes infiltrate the brain in small number, they have been consistently demonstrated to be the most potent leukocyte subpopulation contributing to secondary inflammatory brain injury. However, the exact mechanism of how this minimal number of lymphocytes can profoundly affect stroke outcome is still largely elusive. Here, using a mouse model for ische… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…While this question remains to be definitively answered, microglial reactivation could serve to recruit T-cells 92 and microglial proximity to pericytes and endothelial cells suggest they could present MHC-I to infiltrating T-cells 93 . In turn, T-cells could modulate microglial phenotype 94 . In the APP/PSEN1 model used here, infiltration of T-cells has been reported 95 which means one possibility is that the induction of MHC-I observed here could be to signal to T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…While this question remains to be definitively answered, microglial reactivation could serve to recruit T-cells 92 and microglial proximity to pericytes and endothelial cells suggest they could present MHC-I to infiltrating T-cells 93 . In turn, T-cells could modulate microglial phenotype 94 . In the APP/PSEN1 model used here, infiltration of T-cells has been reported 95 which means one possibility is that the induction of MHC-I observed here could be to signal to T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the present work, immune cells that secrete IFNγ such as T cells and monocytes, which are normally present in the meninges or recruited to sites of injury ( 69 , 70 ), could directly communicate with microglia to regulate mobility. Indeed, a fascinating study ( 71 ) showed that the recruitment of T cells after ischemic stroke, activated microglia in the peri-infarct region (i.e., deramified morphology) and induced gene expression associated with interferon signaling and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the present work, immune cells that secrete IFNγ such as T cells and monocytes, which are normally present in the meninges or recruited to sites of injury 65 , could directly communicate with microglia to regulate mobility. Indeed, a fascinating study by 66 showed that the recruitment of T cells after ischemic stroke, activated microglia in the peri-infarct region (i.e. de-ramified morphology) and induced gene expression associated with interferon signaling and chemotaxis.…”
Section: Discussionmentioning
confidence: 99%